Moral Disengagement, Social Norms, and Motivational Profiles Influence Attitudes Toward Doping Among Spanish Athletics Coaches - García-Grimau, Elena; De la Vega, Ricardo; Casado, Arturo (Frontiers in Sports and Active Living, 2022)
Coaches strongly influence athletes' attitudes towards doping and can shape athlete's beliefs, behaviors, and decisions to be for or against doping. Coached-centered studies examining multiple factors affecting coaches’ doping attitudes and behavior are scarce. The aim of this study was to analyze for the first-time attitudes towards doping in Spanish athletics coaches using the Sport Drug Control Model (SDCM) as a theoretical framework. A secondary aim was to determine the factors in the model predicting attitude and susceptibility toward doping. A cross-sectional study was carried out using a sample consisting of 201 Spanish athletics competitive level coaches from whom 11.4% were female. Participants completed a cross-sectional online survey. Structural equation modeling showed a good fitness of the SDCM. Positive attitudes toward doping predicted high susceptibility to doping (β = 0.39, p < 0.001). Moral disengagement (β = 0.58, p < 0.001), descriptive norms (β = 0.42, p = 0.001), ego-oriented goals (β = 0.34, p < 0.05), and self-efficacy to refrain from doping (β = 0.26, p < 0.05) displayed a significant influence on attitudes toward doping. Self-reported doping prevalence in coaches was 4,5%. These variables should be considered when designing anti-doping research projects and educational programs aiming at modifying coaches’ attitudes towards doping. It is recommended to focus more efforts on coaches, without putting aside the athletes, and therefore turn coaches into reliable doping prevention factors. To this end, it is necessary to enhance scientific research and then develop, implement, and promote more educational programs targeting coaches, on a mandatory basis while covering the specific needs of coaches so that they can perform their role as anti-doping educators in an effective, committed, and proactive manner.